2005
DOI: 10.1080/00071660500098467
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated withSalmonella entericasubsp.entericacontamination of chicken carcases in Senegal

Abstract: The objective of this study was to identify the risk factors for Salmonella spp. contamination of Senegalese chicken carcases during slaughtering. One hundred and twenty traditional slaughterhouses were studied from January 2000 to December 2002 in and around Dakar. A questionnaire was administered to the slaughterers and samples of breast skin were taken to assess the Salmonella spp. status of chicken carcases. Results showed that 43.3% of the chicken batches were contaminated with Salmonella spp., with Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…coli contamination. Our findings were in agreement with other studies that revealed an increase in bacterial contamination on chicken carcasses following the scalding process due to the differences in the scalding temperature, the amount of freshwater added during the scalding process, and the immersion time [ 51 , 52 ]. The findings in this study are also supported by results from several studies [ 53 58 ] that indicate the role of proper scalding process in significantly reduced bacterial contamination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…coli contamination. Our findings were in agreement with other studies that revealed an increase in bacterial contamination on chicken carcasses following the scalding process due to the differences in the scalding temperature, the amount of freshwater added during the scalding process, and the immersion time [ 51 , 52 ]. The findings in this study are also supported by results from several studies [ 53 58 ] that indicate the role of proper scalding process in significantly reduced bacterial contamination.…”
Section: Discussionsupporting
confidence: 93%
“…This finding clearly showed that temperature control during the scalding process significantly reduced bacterial contamination in chicken carcasses. The temperature observed in this study was in agreement with a previous report in Thailand that revealed the temperature of scalding water with the range of 62–66°C [ 59 ], while reports from other countries showed the temperature range between 50–70°C [ 51 , 52 , 56 ].…”
Section: Discussionsupporting
confidence: 92%
“…A high prevalence of the bacteria in live birds increases the risk of contamination of chicken carcasses. [13][14][15] Specific risk factors for Salmonella prevalence in poultry flocks have been studied in production systems in high-income countries, but information on risk factors in traditional or emerging African production systems is scarce. 16 The risk of Salmonella contamination can be high in intensive poultry production, particularly if biosecurity is poor.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the prevalence of Salmonella in fresh broiler meat at slaughter was 50%. High prevalence rates have also been reported in Belgium 46.6% (Daube et al, 2002), in Thailand (66%) (Molla and Mesfin, 2003), in Senegal 43.3% (Cardinale et al, 2005) and in Algeria 70% (Djeffal et al, 2010). In European countries, a recent study showed a lower prevalence rate of Salmonella contamination of chicken carcasses (EFSA, 2015) associated with successful EU Salmonella control programmes for reducing the prevalence of the bacteria in poultry populations, particularly in laying hens.…”
Section: Prevalence Of Salmonellamentioning
confidence: 94%